PENGARUH BEBAN KERJA, STRES KERJA DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA PERAWAT SELAMA MASA PANDEMI COVID-19 DI RSUD DR. ACHMAD MOCHTAR BUKITTINGGI, SUMATERA BARAT - Rahman Putra; Jumiati Sasmita; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Job satisfaction is an employee's assessment, feeling, or attitude towards his workand related to the work environment is entirely a number of wants and needsthrough some work or work desires. The purpose of this study was to determinethe effect of workload, work stress and leadership on nurse job satisfaction duringthe COVID-19 pandemic at RSUD Dr. Achmad Mochtar Bukittinggi. This type ofresearch is descriptive quantitative. The sample in this study amounted to 76people. Data collection techniques using a questionnaire. The data analysismethod uses multiple linear regression analysis techniques with the help of theSPSS version 21 software application. The results of this study indicate that: 1)Workload has a negative and significant effect on nurse job satisfaction, 2) Jobstress has a negative and significant effect on nurse job satisfaction, 3)Leadership has a positive and significant effect on nurse job satisfaction, 4)Workload Work, Job Stress and Leadership have a significant and significanteffect on the job satisfaction of nurses in RSUD Dr. Achmad Mochtar Bukittinggi. Keywords: Job Satisfaction;Workload; Work Stress; Leadership